2015
DOI: 10.1517/13543776.2015.1081168
|View full text |Cite
|
Sign up to set email alerts
|

TBK1 inhibitors: a review of patent literature (2011 – 2014)

Abstract: The role of TBK1 in various diseases has prompted the further investigation of significant targets. Although research on TBK1 inhibitors has increased over the last few years, only a few inhibitors of this kinase have been identified. In addition, almost all of the chemical inhibitors are modified from different scaffolds and/or chemotypes of pyrimidine. Specifically, compound BX795 is the representative one, which was first patented as a potent TBK1 inhibitor. Even though some compounds have displayed interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Next, we analysed LC3 puncta formation and LC3-II induction in fAS-stimulated BV2 GFP-LC3 microglial cells pre-treated with Amlexanox, which has been reported as one of the most specific inhibitors of TBK1 (Reilly et al, 2013;Yu et al, 2015). We observed a marked decrease of both LC3-positive vesicles and relative LC3-II protein levels in cells with impaired TBK1 activity (Fig.…”
Section: Tbk1 Inhibition Impairs Lc3 Recruitment To Damaged Lysosomesmentioning
confidence: 69%
“…Next, we analysed LC3 puncta formation and LC3-II induction in fAS-stimulated BV2 GFP-LC3 microglial cells pre-treated with Amlexanox, which has been reported as one of the most specific inhibitors of TBK1 (Reilly et al, 2013;Yu et al, 2015). We observed a marked decrease of both LC3-positive vesicles and relative LC3-II protein levels in cells with impaired TBK1 activity (Fig.…”
Section: Tbk1 Inhibition Impairs Lc3 Recruitment To Damaged Lysosomesmentioning
confidence: 69%
“…Indeed, pivotal roles for TBK1 and p38 have been reported by several groups, and these proteins were subsequently proposed as putative therapeutic targets for the treatment of arthritis and other inflammatory diseases [23], [24]. In particular, TBK1 is known to be an important enzyme regulating virus-induced inflammatory symptoms [25]. Our recent study found that inhibitory plant extract (ethanol extract of Dryopteris crassirhizoma ) on this enzyme is able to display curative activity against gastritis symptoms stimulated by HCl/EtOH [26].…”
Section: Discussionmentioning
confidence: 99%
“…To further confirm the involvement of TBK and IRF3 in TLR4-induced IFNβ expression in trophoblast cells, we exposed the cells to LPS (100 ng/mL) in the presence or absence of the pTBK inhibitor BX795. 34,35 BX795 is an aminopyrimidine compound that was developed as an inhibitor of the catalytic activity of TBK1 by blocking its phosphorylation.…”
Section: Lps Signaling Induces Type I Ifnβ In Trophoblast Cellsmentioning
confidence: 99%